The pink refrigerator - Egan, Tim, 1957- (Houghton Mifflin, 2007)
Dodsworth does as little work as he can, collecting items from a junkyard and placing them in his thrift store for sale, until he happens upon a pink refrigerator that spurs him to do much more with his life.